2014
DOI: 10.1530/eje-13-0347
|View full text |Cite
|
Sign up to set email alerts
|

Does des-acyl ghrelin improve glycemic control in obese diabetic subjects by decreasing acylated ghrelin levels?

Abstract: Objective: The objective of this study was to assess the effects of a continuous overnight infusion of des-acyl ghrelin (DAG) on acylated ghrelin (AG) levels and glucose and insulin responses to a standard breakfast meal (SBM) in eight overweight patients with type 2 diabetes. Furthermore, in the same patients and two additional subjects, the effects of DAG infusion on AG concentrations and insulin sensitivity during a hyperinsulinemic-euglycemic clamp (HEC) were assessed. Research design and methods: A double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
69
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 37 publications
3
69
1
Order By: Relevance
“…In a recent Letter to the Editor Gaylinn et al (1) discuss the outcomes of a study that we published in the European Journal of Endocrinology in which we reported that the administration of unacylated ghrelin (UAG) improves glycemic control in obese subjects with diabetes and (2) that this effect might be mediated by a decrease in acylated ghrelin (AG) levels in response to UAG administration (2). They comment that, while we clearly demonstrated the anti-diabetogenic potential of UAG, our observation that AG levels are suppressed may be an assay artefact.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent Letter to the Editor Gaylinn et al (1) discuss the outcomes of a study that we published in the European Journal of Endocrinology in which we reported that the administration of unacylated ghrelin (UAG) improves glycemic control in obese subjects with diabetes and (2) that this effect might be mediated by a decrease in acylated ghrelin (AG) levels in response to UAG administration (2). They comment that, while we clearly demonstrated the anti-diabetogenic potential of UAG, our observation that AG levels are suppressed may be an assay artefact.…”
Section: Dear Editormentioning
confidence: 99%
“…Additionally, the blood samples in those two studies were stabilized in a slightly different way. In the study by Ozcan et al (2), whole blood was equilibrated in an acidic isotonic solution containing high concentration of AEBSF and NaF, whereas in Tong et al AEBSF was dissolved in the blood samples and only after preparation of plasma was the sample acidified. 4.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental AG administration commonly causes weight gain and hyperglycemia by enhancing food intake, fat deposition, and hepatic gluconeogenesis (3)(4)(5). A more comprehensive understanding of the metabolic impact of ghrelin has been recently allowed by the increasing appreciation of the independent, and generally more favorable, effects of its unacylated form (UAG), which does not increase food intake or circulating glucose in vivo (3,4,6). Although no specific UAG receptor has been yet identified, UAG coadministration may counteract the glucogenic effects of AG as well as AG-induced hyperglycemia (3,4,7), and positive or negative associations have been respectively reported in humans between AG or UAG and markers of whole-body insulin resistance (8).…”
mentioning
confidence: 99%
“…Moreover, AG-UAG interactions should be systematically investigated in clinical conditions characterized by insulin resistance, when a decline in circulating UAG and higher AG-UAG ratios have been reported (3,4,8). Under these conditions, potential differential modulation by AG and UAG of additional regulators of insulin secretion should be also considered, including autonomic nervous signaling (13), circulating hormones such as growth hormone and cortisol (1,6,19), and dietary carbohydrate intake as shown by Tong et al (19). Finally, the well-demonstrated positive impact of both AG and UAG on b-cell survival and proliferation, leading to enhanced b-cell mass and higher circulating insulin in streptozotocin-induced type 1 diabetes models (10,20), poses important questions; longer-term interactions between altered insulin release and beneficial changes in b-cell mass should be directly investigated during longterm modification of ghrelin profile.…”
mentioning
confidence: 99%